Diversidad de aves en áreas verdes en diferentes condiciones de urbanización y su relación con la estructura de la vegetación, en la ciudad de México - González Palomares, Gerardo (Universidad Autónoma Metropolitana, 2018)
Urbanization is one of the main causes of landscape change and homogenization of species diversity. Given this, green species within cities help to mitigate these negative effects and help preserve the diversity of species. This research addressed the value of green areas for the bird community in sites with different degrees of urbanization. The study areas were chosen because they have different degrees of urbanization. The degree of urbanization was based on different variables associated with the vegetation (coverage of native and introduced species), number of buildings around the park, distance to the nearest natural area and percentage of impermeable surfaces. Bird relative abundance was assessed with fixed radius counting points. The species composition between sites was compared with an Analysis of Similarity (ANOSIM). An analysis of Similarity Percentage (SIMPER) was carried out to define which species contributed with the potential differences. Finally, birds were classified into functional groups in order to calculate functional richness, functional equity and functional divergence. There were 104 species of birds belonging to 31 families and 9 orders in the study sites.The Analyisis of Similartiy showed that bird assemblages were significantly different between sites. The SIMPER test indicates that mainly six urban adapter species contributed to these differences. The functional richness was higher (0.838) in Nativitas Forest, an urban site which is close to natural areas, while the functional equity was higher in Ecoguardas (0.665), a peri-urban site. Both the divergence (0.425) and the functional richness (0.726) was lower in the San Nicolas Totolapan Ejidal Park (PSNT), a natural area, than in the other sites. The high functional diversity in Nativitas is due to the fact that the site is close to natural areas and includes both urban and bird species that are not adapted to live in cities. Finally, the analysis of similarity indicates that in urban areas the characteristic species are those adapted to these environments. This suggests that urbanization is an environmental filter that prevents urban areas from having species that are sensitive to urbanization and those that are restricted in distribution.; Los procesos asociados a la urbanización son una de las principales causas de cambio en el paisaje e igualmente el principal factor de pérdida de biodiversidad. Ante esto, las áreas verdes mitigan esos efectos negativos y ayudan a preservar la diversidad de especies. En esta investigación se abordó el valor de las áreas verdes para la comunidad de aves en sitios con diferente grado de urbanización, de marzo de 2016 a febrero de 2017. Las zonas de estudio se eligieron por que presentan distintos grados de urbanización. La urbanización se estimó con base a distintas variables asociadas a la vegetación (cobertura de especies nativas e introducidas), número de construcciones alrededor del parque, distancia al área natural más cercana y porcentaje de superficies impermeables. La abundancia de las aves se obtuvo a partir del método de puntos de conteo de radio fijo. Para comparar la similitud de las comunidades, se realizó un análisis de similitud (ANOSIM). Posteriormente se realizó un análisis del porcentaje de similaridad (SIMPER) para delimitar que especies hacen la diferencia. Por último, las especies se clasificaron en grupos funcionales y se calculó la riqueza funcional, equidad funcional y divergencia funcional. Se registraron 104 especies de aves pertenecientes a 31 familias y 9 órdenes. El ANOSIM fue significativo con todas las áreas verdes. La prueba de SIMPER indicó que seis especies son las que hacen la diferencia entre los parques y son urbanofilicas. La riqueza funcional fue mayor (0.838) en el Bosque de Nativitas, un sitio urbano, mientras que la equidad funcional fue mayor en Ecoguardas (0.665), un sitio periurbano. La divergencia (0.425) y la riqueza funcional (0.726) fue más baja en el Parque Ejidal San Nicolás Totolapan (PSNT) que en los otros sitios. La alta diversidad funcional en Nativitas se debe a que el sitio está cerca de áreas naturales e incluye tanto especies urbanófilas como aves que no están adaptadas a vivir en las ciudades. Finalmente, el análisis de similitud indica que en zonas urbanas las especies características son las adaptadas a estos ambientes. Esto sugiere que la urbanización es un filtro ambiental que impide que en las áreas urbanas cuenten con especies sensibles a la urbanización y aquellas de distribución restringida.